Wujud Bahasa Arab dalam Memperkaya Kebudayaan Indonesai - Novita Rahmi (Institut Agama Islam Negeri Metro, 2018)
Arabic language influence Indonesian culture along with the arrival of Arab traders to Indonesia in the 7th century Masehi, the first time they entered Indonesia through India (Gujarat) to trade, then continues as a propagator of Islam. Although Indonesia experienced an acculturation process with Hindu-Buddhist, Dutch, Japanese and other cultures, Arabic also made a huge contribution to the growth of Indonesian as a national language. Until now the form of Arabic can still be seen in various aspects of culture in Indonesia. In terms of language, there are many words that come from the Arabic words Likewise with art, Arabic is written with beautiful writing / calligraphy until now is used to decorate the mosque building and become one of the branches of MTQ. Customs in Indonesia are also heavily influenced by Arabic, sekaten ceremonies, ruwahan, etc. are evidence of Arabic acculturation in Indonesia.